Comparison of sustained attention skills of deaf athletes and nonathletes - Gur, Yunus; Gencay, Selcuk; Gur, Ercan (Mehmet Tekerek, 2017)
In this research it is aimed to compare the attention skills of hearing-impaired children playing sports and who do not. In total, 233 hearing-impaired children living in the cities; Malatya, Elazig, Gaziantep and Istanbul participated to the research. SPSS program were used for statistical analysis of the data obtained in the study and the level of statistical significance was determined as (p < .05). At the end of the research, it has been found that the attention levels of hearing-impaired children who play sports show statistically significant difference according to their gender (p < .05). As a result, it seems that when it is compared with hearing-impaired children who do not play sports, the demographic variables have a lower impact on the attention levels of the ones, who play sports.
Keywords: Impairment; hearing impairment; children; sport; attention level